The four-component two-particle propagator for the calculation of double-ionization spectra of heavy-element compounds: I. method - Pernpointner, Markus (Journal of physics. B, Atomic, molecular and optical physics, 2010)
In this work we present a new four-component implementation of the two-particle (2p) propagator as a powerful tool for calculating double-ionization spectra of systems containing heavy elements. The 2p-propagator approach provides immediate access to the complete final state distribution of doubly ionized systems together with a detailed configurational information of each final state. This information is vital for the analysis of electronic decay processes as radiationless relaxation mechanisms after an initial core hole ionization and for the simulation of Auger spectra. The capabilities of the four-component realization are first demonstrated at the xenon atom and the bromine molecule for which experimental results are available. It turns out that a relativistic treatment is required for an adequate description of the experimental findings. In this first paper we focus on the electronic structure described by the 2p propagator and will later on apply this method to the calculation of Auger spectra and electronic decay processes in heavy systems.
Gesehen am 28.04.2023